2022
DOI: 10.3928/01477447-20220128-07
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Extreme Transforaminal Lumbar Interbody Fusion With Large Spacers: A Technical Note and Preliminary Report

Abstract: This report describes a novel endoscopic fusion technique performed with unilateral biportal endoscopy (UBE) that is known as extreme transforaminal lumbar interbody fusion (eXTLIF) and is performed with a large spacer. We also present the short-term results of this procedure. Previous studies reported that minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) could achieve acceptable rates of fusion; therefore, it is often used for treating various degenerative lumbar diseases. Moreover, MIS-TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To ensure the integrity of the data, a screening of included studies in recent UBE reviews 30-33 and identified 4 additional studies that were subsequently incorporated into this research. 34-37 The specific search process is shown in Figure 1.
Figure 1.Flow diagram of study selection.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure the integrity of the data, a screening of included studies in recent UBE reviews 30-33 and identified 4 additional studies that were subsequently incorporated into this research. 34-37 The specific search process is shown in Figure 1.
Figure 1.Flow diagram of study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…However, to properly install the giant OLIF cage in the Ex-TLIF approach, not only a higher inclined angle is required, but also an additional paravertebral portal is made for the insertion of a large OLIF cage. 24 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the short-term radiological results of the two groups were analyzed, OLIF-AF group was superior to the ULIF group in terms of DH recovery, and the rate of improvement in the LL and Segmental angle was better in the OLIF-AF group compared to ULIF group, which may be related to the use of a larger size cage in OLIF-AF group. Eum et al [ 24 ] conducted a retrospective study on 22 patients, all patients underwent extreme transforaminal lumbar interbody fusion (eXTLIF) in unilateral biportal endoscopy (UBE) and used a large profile fusion cage. The follow-up time was more than 6 months, and satisfactory results were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Successful intervertebral fusion depends on thorough intervertebral disc removal and endplate preparation with a greater contact area. [ 36 ] In comparison to traditional methods, ULIF enables the surgeon to view the interbody incision and vertebral endplate using magnified endoscopy. This helps the surgeon avoid excessive or insufficient scraping of the bearing bone surface and lowers the risk of postoperative fusion descent or displacement.…”
Section: Discussionmentioning
confidence: 99%